2018
DOI: 10.3390/su10093058
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Readiness to Reduce Meat Consumption for the Purpose of Environmental Sustainability: Insights from Norway

Abstract: Food production is associated with various environmental impacts and the production of meat is highlighted as a significant source of greenhouse gas emissions. A transition toward plant-based and low-meat diets has thus been emphasised as an important contribution to reducing climate change. By combining results from a consumer survey, focus group interviews and an in-store field experiment, this article investigates whether Norwegian consumers are ready to make food choices based on what is environmentally su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 75 publications
4
58
2
1
Order By: Relevance
“…Although previous literature indicates that knowledge is a necessary determinant to perform environmentally responsible behavior [e.g., Austgulen et al (2018)], in the present study the change in knowledge did not predict the change in attitude toward eating less meat. It seems that the effect of the exposure to Cowspiracy is mediated or can be explained by other variables.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Although previous literature indicates that knowledge is a necessary determinant to perform environmentally responsible behavior [e.g., Austgulen et al (2018)], in the present study the change in knowledge did not predict the change in attitude toward eating less meat. It seems that the effect of the exposure to Cowspiracy is mediated or can be explained by other variables.…”
Section: Discussioncontrasting
confidence: 97%
“…In recent years, the entertainment business and popular documentaries such as Cowspiracy, Forks Over Knives, and What the Health have played a central role in the public awareness of the environmental implications of meat consumption (Harrington et al, 2019). This seems to contradict with past and current research that has shown that using environmental arguments to eat less meat do not make campaigns for meat reduction successful (Cordts et al, 2014;Austgulen et al, 2018). These authors have suggested that using arguments related to one's personal health or the wellbeing of animals are more effective (Cordts et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many individuals are unaware of the environmental impacts of meat eating (Austgulen, Skuland, Schjøll, & Alfnes, 2018;Tobler, Visschers, & Siegrist, 2011). Instead, meat-reducing behaviours are often motivated by health concerns (e.g., Tobler et al, 2011), although many meat-eaters believe that vegetarian diets are nutritionally unbalanced .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, consumers are allocated with a large share of the responsibility for environmental sustainability, having a major role in making food chains more sustainable [101]. That is why, in the context of food, one of the most important contributions of consumers to the reducing climate change, as Austgulen et al [102] claims, could be the transition towards a plant-based and low-meat diet, what means a flexitarian food style. Although most consumers are still not ready to make food choices based on what is best for the climate or environment, they are expected to be more aware of this responsibility in the near future.…”
Section: H6: the Social Media Usage On Healthy Eating Is Positively Rmentioning
confidence: 99%